2021
DOI: 10.1186/s12931-021-01757-1
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB10 contributes to asthma by inhibiting the apoptosis of allergenic Th2 cells

Abstract: Background Serine peptidase inhibitor, clade B, member 10 (SERPINB10) contributes to allergic inflammation in asthma. However, its role in the T-helper type 2 (Th2) response of allergic asthma is not known. The goal of this study was to unveil the function of SERPINB10 in the Th2 response of allergic asthma and the mechanism by which SERPINB10 affects the viability of Th2 cells. Methods Th2 cytokines and serum levels of house dust mite (HDM)-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Here, we show for the first time that SERPINB10 expression was significantly increased in induced sputum in asthmatic patients. This is consistent with previously reported increases in asthmatic airway epithelium and lung tissue in HDM/OVA asthmatic mice [16]. Increased SER-PINB10 expression in induced sputum in patients with asthma may be due to secretion of airway epithelial cells or other inflammatory cells, such as lymphocytes or eosinophils.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we show for the first time that SERPINB10 expression was significantly increased in induced sputum in asthmatic patients. This is consistent with previously reported increases in asthmatic airway epithelium and lung tissue in HDM/OVA asthmatic mice [16]. Increased SER-PINB10 expression in induced sputum in patients with asthma may be due to secretion of airway epithelial cells or other inflammatory cells, such as lymphocytes or eosinophils.…”
Section: Discussionsupporting
confidence: 93%
“…Down-regulation of SER-PINB10 expression reduces airway hyperresponsiveness and eosinophilic inflammation in a mouse model of asthma. We also found that SERPINB10 may be involved in inhibiting asthma allergic inflammation and Th2 response by inhibiting Th2 cell apoptosis [16]. However, the expression of SERPINB10 protein in induced sputum and its relationship with airway type 2 inflammation in asthma remain unclear.…”
Section: Introductionmentioning
confidence: 81%
“…Studies showed that increased levels of SERPINB10 mRNA in epithelial cells of patients with asthma can lead to allergic airway inflammation, which is positively correlated with AHR, sputum eosinophil percentage, and exhaled nitric oxide content ( 50 ). Interestingly, the stimulation of T cell receptor with anti-CD3 antibody can upregulate the expression of SERPINB10 in Th2-polarized cells but has no effect on the expression of SERPINB10 in Th1-polarized cells, proving that it is a stable marker in non-Th2-type asthma ( 51 ). Severe asthma is dominated by Th1/Th17 cytokine responses and rarely has a Th2-mediated immune imbalance ( 52 ), whereas this phenomenon is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms underlying asthma are unclear, some of these hub genes are under investigation [ 23 29 ]. For example, CST1 is a member of the type 2 cystatin (CST) superfamily, which is known to inhibit the proteolytic activities of cysteine proteases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ITLN1 is a biomarker associated with disease susceptibility in asthma [ 28 ]. A study on ERPINB10-knockdown mice found that these groups of mice had diminished numbers of Th2 cells and were more susceptible to apoptosis, indicating that SERPINB10 may contribute to allergic inflammation and the Th2 response of asthma by inhibiting the apoptosis of Th2 cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%